1997
DOI: 10.1063/1.364027
|View full text |Cite
|
Sign up to set email alerts
|

SiGeC alloy layer formation by high-dose C+ implantations into pseudomorphic metastable Ge0.08Si0.92 on Si(100)

Abstract: Dual-energy carbon implantation (1ϫ10 16 /cm 2 at 150 and at 220 keV͒ was performed on 260-nm-thick undoped metastable pseudomorphic Si͑100͒/ Ge 0.08 Si 0.92 with a 450-nm-thick SiO 2 capping layer, at either room temperature or at 100°C. After removal of the SiO 2 the samples were measured using backscattering/channeling spectrometry and double-crystal x-ray diffractometry. A 150-nm-thick amorphous layer was observed in the room temperature implanted samples. This layer was found to have regrown epitaxially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…However, due to the low solubility of carbon in Si, β-SiC can be formed during epitaxial regrowth. [6][7][8]12) Moreover, because carbon retards the SPE rates, a higher regrowth temperature is necessary. [13][14][15][16] Despite these conflicting problems, Strane et al [14][15][16] have shown that carbon can be successfully incorporated into the substitutional sites using ion implantation followed by SPE.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low solubility of carbon in Si, β-SiC can be formed during epitaxial regrowth. [6][7][8]12) Moreover, because carbon retards the SPE rates, a higher regrowth temperature is necessary. [13][14][15][16] Despite these conflicting problems, Strane et al [14][15][16] have shown that carbon can be successfully incorporated into the substitutional sites using ion implantation followed by SPE.…”
Section: Introductionmentioning
confidence: 99%
“…This prospect would allow for tuning the lattice constant and band gap independently by adjusting the composition ratios and offers an additional degree of freedom for band gap engineering, which is not attainable by standard Si technology or SiGe heteroepitaxy [6]. However there are limitations on achieving complete substitution due to the low solubility of C in Si and the tendency of carbon to form silicon carbide, or C-C bonds [5].The energy band gaps and the lattice constants of the alloy are important parameters for device design. However, very little theoretical or experimental work on the alloy Si 1ÀxÀy Ge x C y has been reported.…”
mentioning
confidence: 99%
“…Incoporation of a low carbon concentration into substitutional sites of SiGe might be able to relieve the inherent strain of the SiGe layers grown on a Si substrate [1][2][3][4][5] while changing the band gap energy. This prospect would allow for tuning the lattice constant and band gap independently by adjusting the composition ratios and offers an additional degree of freedom for band gap engineering, which is not attainable by standard Si technology or SiGe heteroepitaxy [6].…”
mentioning
confidence: 99%
“…Assim, o carbono atua como um redutor de parâmetro de rede da liga cristalina temária SiGeC. Desta forma, obtém-se um material com boas propriedades do SiGe e com um parâmetro de rede adequado para o silicio [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Motiva Cãounclassified